Effects of Late Summer Prescribed Fire on Botanical Composition, Soil Cover, and Forage Production in Caucasian Bluestem-Infested Rangeland in the Kansas Smoky Hills: Year 2 of 4 - M. P. Ramirez; A. J. Tajchman; Z. M. Duncan; J. Lemmon; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective was to document the effects late-summer prescribed fire on soil cover, botanical composition, and forage production in the Kansas Smoky Hills and the associated effects on dense Caucasian bluestem (Bothriochloa bladhii) stands therein. Study Description:The study took place on a private ranch in Ellsworth County, in the Kansas Smoky Hills. Eighteen one-acre plots were assigned randomly to one of three prescribed-fire treatments: no burn, single burn (i.e., one burn treatment only in 2019), or biennial burn (i.e., two burn treatments in 2019 and 2021). Soil cover, plant composition, and forage production were evaluated annually. These data represent plant community effects one year following prescribed fire. The Bottom Line:The data were interpreted to indicate that one year of late-summer prescribed fire was associated with decreased presence of Caucasian bluestem and increased native plant richness, a component of biological diversity, but was not associated with clear trends for change in forage production. A second fire treatment is planned for 2021.
Keywords: botanical composition; old-world bluestems; prescribed burning